Espejismos - Ureña Arroyo, Jurgen; Ovares Gutiérrez, Tobías ([San José, Costa Rica] : La Ventana, 2007)
Sumario: Presenta la vista de un día en el Parque Central de San José a través de un espejo.
Cortometraje--Créditos: Fotografía, Ernesto Villalobos, Jurgen Ureña ; sonido, Francisco González, Mauro Borges ; edición, Mauro Borges
Keywords: PARQUE CENTRAL (SAN JOSE, COSTA RICA) -- VIDA SOCIAL Y COSTUMBRES; PARQUE CENTRAL (SAN JOSE, COSTA RICA) -- MATERIALES AUDIOVISUALES